HUBUNGAN IBU HAMIL PEROKOK PASIF DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH DI RUMAH BERSALIN IBU SRI PANUNTUN KLATEN - Sri Aminingsih; Nadiya Istiqomah (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2018)
Background: Smoking affects blood circulation and makes mothers and babies exposedto hazardous chemicals. Every time a mother smokes, her baby gets less oxygen.Nicotine in cigarettes decreases blood flow to the placenta. At the same time carbonmonoxide (CO) lowers the amount of oxygen carried by blood. In addition, there are toxicchemicals that usually interfere the development of infants (Rahmalia, 2009). Apreliminary study conducted by the author at the Maternity House of Sri Panuntun, PedanKlaten District, there were 30 babies born in August to September 2017, revealed thatthere were 6 babies suffered from low birth weight, while 24 babies have normal birthweight.The purpose: Describing the relationship of pregnant women passive smokers with theincidence of Low Birth Weight was the aim of this study.The subjects : The population in this study was all mothers who gave birth at MaternityMother Sri Panuntun Klaten in January-March 2018 accounted for 55 respondents.The results: The result of this research by using Pearson Chi-Square correlation testobtained p = 0.000.The conclusion: There was a positive correlation between pregnant women who arepassive smokers with the incidence of low birth weight babies.Keywords: Pregnant women, Passive smokers, Low birth weight babies.